Nutritional Status of Patients Starting on Peritoneal Dialysis: A Comparison Between Planned and Unplanned Dialysis Initiation - Silva, Maryanne Zilli Canedo [UNESP]; Avesani, Carla Maria; Vogt, Barbara Perez; Costa, Fabiana Lourenço [UNESP]; Ponce, Daniela [UNESP]; Lindholm, Bengt; Caramori, Jacqueline Costa Teixeira [UNESP] (Elsevier, 2025)
Objective: A suboptimal dialysis initiation with insufficient or no planning before urgent start of dialysis remains a common problem associated with increased morbimortality. Whether nutritional markers differ between patients starting peritoneal dialysis (PD) in unplanned and planned modes has not yet been explored. Therefore, we aimed to evaluate whether the nutritional status at the start of dialysis differed between patients with unplanned and planned PD initiation. Methods: In this observational study comprising 47 adult patients starting PD (age 58 ± 15 years, 51% female), 29 patients had unplanned (starting dialysis up to 72 hours after peritoneal catheter implantation) and 18 planned (follow-up predialysis >90 days) dialysis initiation. Within 30 days of PD initiation, nutritional status was evaluated using anthropometric measurements, multifrequency bioelectrical impedance analysis, appetite assessment, handgrip strength, laboratory markers, and the malnutrition-inflammation score. Physical activity and performance were also evaluated. Results: Patients with an unplanned PD initiation had a higher frequency of diabetes, higher blood glucose, urea, and glycated hemoglobin levels, and lower hemoglobin and albumin levels. Furthermore, they had a lower calf circumference, slower gait speed, higher protein intake, and greater malnutrition-inflammation score, while their physical activity level and appetite did not differ. Conclusion: Patients with an unplanned PD had unfavorable clinical and nutritional markers compared with those with planned PD. These findings indicate that a lack of follow-up prior to dialysis initiation can influence the clinical and nutritional statuses of patients, reinforcing the importance of conservative treatment prior to dialysis initiation.
Keywords: conservative kidney care; Kidney failure; nutritional status; peritoneal dialysis; unplanned dialysis initiation